Does Education Affect Environmental Crime? A Dynamic Panel Data Approach at Provincial Level in Italy - Castaldo, Angelo (International criminal justice review, 2023)
This article investigates the role of education on environmental crime in Italy using a panel of 110 Italian provinces over the period 2010–2015. We employ a system-GMM (Generalized Method of Moments) dynamic panel data approach to tackle the endogeneity that might arise in the estimations from the environmental crime dynamic path and to consider time-invariant effects on provinces. Our empirical results, even after controlling for socioeconomic and judicial efficiency characteristics, support the existence of a U-inverted relationship between education and environmental crime, which depicts an unconventional finding: At the margin, a higher level of education endowment offsets the propensity to commit environmental crimes, which are confirmed to be white-collar type of crimes. The results are robust to model specifications and endogeneity. Furthermore, to check the robustness of nonmonotonicity in the relationship between environmental crime and education and to control for unobserved provincial heterogeneity, we also exploit a semiparametric fixed effects model. There is wide room for efficiency gains that could arise from policy interventions aiming to put environmental crimes into perspective.